PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERBANKAN INDONESIA (STUDI EMPIRIS DI BURSA EFEK INDONESIA TAHUN 2015-2017) - Ahmad Badawi (Universitas Mercu Buana, 2018)
The Company's Financial Performance is a form of corporate transparency and accountability to public and affects investor confidence. In accordance with OJK rules require that the company, especially the banking in its management must apply the principles of transparency, accountability, responsibility, independency, and fairness, so that will build the company's fundamentals. This study aims to prove empirically the influence of GCG (number of directors, number of independent commissioners and the number of audit committee meetings) and Intellectual capital on the performance of banking companies. The sample of this study used purposive sampling and number of banks as much as 32 Conventional Banks in Indonesia with the study period of 2015 -2017. This study used panel data regression analysis with Eviews 10 analysis tool. The results of this study showed that GCG variable (independent commissioner influential, directors variable and number of meetings did not have significant effect) and IC have significant effect on company performance.